Epiisopiloturina de Pilocarpus microphyllus inibe a resposta inflamatória de células microgliais induzida por LPS interferindo na via de sinalização TLR4/NF-B-MAPKs - Sousa, João Antônio Costa de (2022)
Neuroinflammation is present in the pathophysiological mechanisms of several diseases that affect the central nervous system. In this context, the microglia have a prominent role in initiating and sustaining the inflammatory process. Epiisopiloturine (EPIT), an imidazole alkaloid obtained from the by-product of pilocarpine extraction from Pilocarpus microphyllus (jaborandi), has shown to be a promising drug with anti-inflammatory and antinociceptive properties. Given the above, the present study aimed to investigate the effect of EPIT on the inflammatory response of microglial cells (BV2 cells) induced by LPS and elucidate its possible mechanism of action. Initially, the probability of EPIT to cross the blood-brain barrier (BHE) was evaluated predictively by using the Swiss ADME online platform. The cytotoxicity of EPIT per se (3.5; 35; 87.5; 175 and 350 µM) and under LPS stimulation (0.5 μg/mL), was evaluated using the lactate dehydrogenase (LDH) enzyme activity assay and by the MTT test. The effect of this alkaloid on microglial cells exposed to LPS (0.5 μg/mL) was investigated by determining the concentration of pro-inflammatory mediators such as nitric oxide/nitrite (EPIT: 3.5 - 350 µM), IL-1β, IL-6 and TNF-α (EPIT: 87.5 µM) and anti-inflammatory mediators such as IL-10 (EPIT: 87.5 µM), as well as by determining the effect of EPIT on iNOS enzyme expression. Western blot analysis was also employed to determine the effect of this molecule (EPIT: 87.5 µM) on pro-and anti-inflammatory signaling pathways, evaluated by the expression of transmembrane receptors (TLR4/TREM2), the NF-κB and MAPKs (JNK and ERK 1/2). EPIT showed a high ability to penetrate the BHE, and up to the concentration of 350 μM did not alter LDH activity, as well as did not interfere with cell viability assessed by the MTT test. Pretreatment with EPIT (35; 87.5; 175 and 350 µM), significantly reduced nitrite production and iNOS enzyme protein expression. Regarding cytokine production, EPIT (87.5 µM) reduced IL-6 and TNF-α production by up to 40 % and 34 %, respectively, with emphasis on its effect on IL-1β concentration (LPS+EPIT: 57.0 ± 14.4 pg/mL) that did not differ statistically from the RPMI/basal group (44.1 ± 3.6 pg/mL). However, EPIT did not increase the concentration of IL-10 reduced by LPS in BV2 cells. EPIT inhibited the TLR4/NF-κB-MAPKs (JNK and ERK1/2) signaling pathway by suppressing the expression of phosphorylated proteins, but did not interfere with TREM2 receptor expression in LPS-exposed cells. The study determined, in a novel way, the anti-inflammatory effect of EPIT in microglial cells, which appears to be associated with the suppression of the signaling cascades of NF-κB and MAPKs (JNK and ERK1/2) by affecting the expression of the TLR4 receptor, associated with pro-inflammatory mechanisms.